Pelatihan dan Penyuluhan Pemanfaatan Potensi Ikan Bandeng di Desa Semampir Kabupaten Gresik Sebagai Produk Bernilai - Effendi, Prihatin; Puspitasari, Dara; Nasichin, moh; Wachidiyah Ningsih, Dwi; Vitria, Yati; mashudi, Mashudi (Jurnal Abdimas Multidisiplin, 2024)
Community service activities have been carried out in the form of training and counseling on the utilization of the potential of the Semampir Village area in the form of processing milkfish to produce milkfish brains, presto milkfish and thornless milkfish. Milkfish as the main commodity of Semampir Village is sold at low prices, especially during the harvest season, so that the profits of pond farmers are very limited. The existence of this service activity is expected to increase the ability and knowledge of the community regarding how to process milkfish into milkfish otak-otak products, presto milkfish and tampa thorn milkfish with high nutritional value, as well as provide knowledge for the community on how to package products by prioritizing hygiene and product marketing through the media. social. The results obtained from this service activity are the achievement of an increase in the economic value of the commodity in the Semampir Village area in the form of milkfish and an increase in housewives who are members of the PKK organization in processing, packaging and marketing the products produced.